Anomaly of the inferior vena cava and its tributaries - O. A. Kaplunova; E. V. Chaplygina; O. P. Sukhanova; Z. A. Goncharova; N. A. Kornienko; E. D. Stefanova (Медицинский вестник Юга России, 2023)
Detection of a combination of aplasia of the inferior vena cava and retroaortic left renal vein is extremely rare. A description of a clinical case with similar anomalies in the development of the inferior vena cava and the left renal vein is given. In our case, the combination of an anomaly of the inferior vena cava and the left renal vein in a 59-year-old male patient was an incidental finding during examination and treatment for acute cerebrovascular accident. Asymptomatic aplasia of the prerenal and hepatic sections of the inferior vena cava with drainage into the azygous vein was revealed. The hepatic veins empty into the right atrium. The identified variant of aplasia of the prerenal and hepatic sections of the inferior vena cava with drainage into the unpaired vein is the result of atrophy of the right subcardinal vein. A rare unclassified type of retroaortic left renal vein was found, the lower branch of which flows into the inferior vena cava, and the upper branch into the unpaired vein. The retroaortic left renal vein is formed while maintaining the anastomosis between the right and left supracardinal veins. The possibility of accidental radiographic findings of anomalies in the development of the inferior vena cava and its tributaries in humans before clinical manifestations has been established. Given the possible manifestation of an anomaly of the inferior vena cava in people over 40 years of age with a clinic of peripheral venous thrombosis, and the manifestation of the retroaortic left renal vein - the development of congestive venous hypertension in the kidney, the patient was given the necessary recommendations.